Fiber-reinforced polyurethane matrix composites for engineering applications - Sharma, Anurag (American Chemical Society, 2024)
Fiber-reinforced polymer (FRP) composites have widespread engineering applications owing to their specific strength and specific stiffness. However, one of the main issues related to FRP composites is their polymeric constituent used as the matrix. Many engineering polymers used in composites are expensive, require complex manufacturing processes, and are not very environmentally friendly. This has motivated researchers to explore the use of versatile polyurethane (PU) as a matrix material for FRP composites, which can offer excellent flexibility, reduced cost, lower weight, mechanical robustness, and biodegradability in some variants. Nevertheless, it is important to understand the viability and performance of fiber-reinforced polyurethane matrix (FRPUM) composites when subjected to mechanical loading, such that their usage in engineering applications is established. This chapter introduces the basic concept of FRPUM composites and examines their mechanical performance in engineering applications. A comprehensive comparison is made among the relevant published literature. Based on this, developments and potential challenges in various engineering fields—such as automobiles, oil and gas industries, electromagnetic interference shielding, building and construction, and sports—are discussed and reported. Finally, future directions and conclusions are presented. This chapter demonstrates that FRPUM composites have the potential to serve as cost-effective, lightweight, and sustainable alternatives to commercially available FRP composites.